Pengaruh Penggunaan Video Animasi Interaktif Terhadap Keterampilan Menyimak Siswa Pada Pembelajaran Bahasa Indonesia Kelas II SDN 2 Bakan, Lombok Tengah, NTB - Sriningsih Sriningsih (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Language is a fundamental social phenomenon, inherently connected to the community that uses it. In the context of primary education at SDN 2 Bakan, the challenge lies in bridging the gap between basic linguistic knowledge and practical communicative skills. Traditional methods often fail to capture the sociocultural nuances of language, leading to students who may understand grammar but struggle with contextual appropriateness.This study aims to analyze the implementation of a sociolinguistic-based approach using interactive animation videos to enhance students' communicative competence and listening skills.This research employs a qualitative descriptive method with a literature review approach. Data were collected through the search and analysis of academic documents, including scientific journals, books, and proceedings from databases such as Google Scholar. The data were analyzed using thematic content analysis to identify key patterns and concepts.Findings indicate that interactive animation videos allow for authentic discourse analysis, role-play simulations, and discussions on language variation. This approach has a positive impact on students' understanding of language registers, politeness, and contextual usage, ultimately improving their pragmatic and sociocultural competencies. Sociolinguistics acts as a vital bridge between linguistic theory and practical communication. Integrating this approach is essential for preparing primary school students for real-world social interactions.